Risk stratification for nonagenarians undergoing transcatheter aortic valve replacement. Issue 2 (15th November 2019) - Yu, Pey‐Jen; Catalano, Michael; Palazzo, Robert; Cassiere, Hugh; Kohn, Nina; Rutkin, Bruce; Maurer, Greg; Berg, Jacinda A.; Hartman, Alan
Abstract: Background: There are disparate data on the outcomes of nonagenarians undergoing transcatheter aortic valve replacement (TAVR) compared with younger patients. The purpose of this study is to determine whether the Society of Thoracic Surgeons (STS) score can be used to identify the subset of nonagenarians that are at a significantly higher risk for poor postoperative outcomes after TAVR. Methods: A total of 425 patients above the age of 80 underwent elective TAVR between 12/2013 and 2/2018 and were included in this study. Patients were deemed intermediate or high risk based on an STS predicted the risk of surgical mortality score of 3% to 8% and more than 8%, respectively. Differences in postoperative outcomes and/or 6‐month mortality between intermediate and high‐risk octogenarians and nonagenarians were compared. Results: Of the 425 patients, 112 (26.4%) patients were nonagenarians, and 313 (73.6%) patients were octogenarians. Fifty‐four (48.2%) of the nonagenarians were stratified as high‐risk, while 78 (24.9%) of the octogenarians were stratified as high‐risk. There were no statistically significant differences in the composite outcomes between intermediate‐risk nonagenarians and intermediate‐risk octogenarians. In contrast, high‐risk nonagenarians were significantly more likely to experience the composite outcome of major perioperative complications and/or 6‐month mortality as compared to high‐risk octogenarians. Conclusion: Intermediate‐risk nonagenarians undergoing TAVR have similar postoperative outcomes compared to intermediate‐risk octogenarians. However, high‐risk nonagenarian patients undergoing TAVR experience significantly poorer outcomes compared to their octogenarian counterparts. Judicious patient selection for TAVR in this subgroup of patients is therefore warranted.